The Gut Microbiota and Short-Chain Fatty Acids Profile in Postural Orthostatic Tachycardia Syndrome - Ishimwe, Jeanne A.; Breier, Nicholas; Saleem, Mohammad; Kastner, Paul D.; Kirabo, Annet; Shibao, Cyndya A. (Frontiers in Physiology, 2022)
Postural orthostatic tachycardia syndrome (POTS) is a devastating chronic form of orthostatic intolerance associated with excessive heart rate increase without hypotension during upright posture. POTS patients exhibit increased circulating norepinephrine levels with exaggerated sympathetic nervous system response upon standing. Emerging evidence suggests a role of the gut microbiome in cardiovascular disorders. However, the etiology of POTS and whether the gut microbiome plays a role are not fully elucidated. We assessed whether the gut microbiome and fecal short-chain fatty acids were different in POTS patients compared to healthy control women. Patient underwent hemodynamic measurements while supine and upon standing. Fecal samples were collected and analyzed using shotgun sequencing and Liquid Chromatography-High Resolution Mass Spectrometry and dietary habits were measured with a fitness application. We found that POTS patients in the standing position had higher circulating norepinephrine and epinephrine levels and increased heart rate. There were no differences in diet composition between groups. Of note dietary salt intake was also similar despite the fact that these patients are advised to consume a high salt diet. Alpha and beta diversity were similar between groups. We observed no differences in bacteria at the phylum levels of Firmicutes to Bacteroidetes ratio. Interestingly, we found that Lachnoclostridium and Parabacteroides genera were higher in POTS when compared to the control group. On the other hand, Coprococcus, Coprobacter, and Monoglobus were lower in POTS patients compared to controls. We also found that both POTS patients and healthy controls had similar levels of short-chain fatty acids. These results suggest POTs per se may have limited effects on gut microbiota composition and derived short chain fatty acids. Further studies are needed to assess the role of the alterations observed at the genus level.